MAIN REASONS OF VES CURVES DISTORTION IN VOLCANIC REGIONS, THEIR CLASSIFICATION AND APPLICATION POSSIBILITIES (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
To solve practical problems, in particular for well-drilling, it is necessary to introduce methodical changes, which will make possible to show near-surface discontinuity. Using these methods we can qualify and improve some field data and interpret the received findings for using them in mapping.
Keywords: well-drilling; VES curves noise; horizontal layered medium